Women in the sky : gender and labor in the making of modern Korea - Nam, Hwasook, 1959- (Ithaca [New York] : ILR Press, an imprint of Cornell University Press, 2021)
"This book examines Korean women factory workers' century-long activism from the 1920s to the present in broad historical context with a focus on gender politics in the labor movement and in the larger society"--
A "woman-in-the-sky": female workers on strike in colonial Pyongyang -- Factory women in the socialist imagination: the 1930s -- Coping with women strikers: nation, class, and gender under colonial rule -- Factory women in the postwar settlement -- Women workers in industrializing Korea -- Female strikers in recent decades and the politics of memory
Includes bibliographical references and index
Description based on online resource; title from digital title page (viewed on July 27, 2021).
JSTOR
Keywords: Women in the labor movement -- Korea -- History -- 20th century; Women in the labor movement -- Korea (South) -- History -- 20th century; Women in the labor movement -- Korea (South) -- History -- 21st century; Manufacturing industries -- Korea -- Employees; Manufacturing industries -- Korea (South) -- Employees; Women employees -- Political aspects -- Korea; Women employees -- Political aspects -- Korea (South); Femmes dans le mouvement ouvrier -- Corée -- Histoire -- 20e siècle.; Femmes dans le mouvement ouvrier -- Corée du Sud -- Histoire -- 20e siècle.; Femmes dans le mouvement ouvrier -- Corée du Sud -- Histoire -- 21e siècle.; Industrie manufacturière -- Corée -- Personnel; Industrie manufacturière -- Corée du Sud -- Personnel; Personnel féminin -- Aspect politique -- Corée.; Personnel féminin -- Aspect politique -- Corée du Sud; HISTORY / Asia / Korea; Manufacturing industries -- Employees; Women in the labor movement; Korea; Korea (South); 1900-2099; Electronic books; History